KASPAROV VERSUS DEEP BLUE: AN ILLUSTRATION OF THE LUCAS GÖDELIAN ARGUMENT. - Hankey, Alex (Cosmos & History, 2021)
This article concerns philosophy of mind, in particular the question, is the human mind more than a digital machine? A previous article took up that question from the perspective of the Lucas Gödelian Argument, which proposed an answer to the question from the point of view of metamathematics. That article pointed out that, the present full scientific status for direct mind-to-mind communication, demonstrates a field of phenomena where no computer can hope to imitate human and animal abilities. This article aims to disprove the argument put forward by the IBM team that programmed the Deep Blue computer, that because their computer beat World Champion at Chess, Garry Kasparov, Deep Blue was more powerful than the human mind. To do this, the article recounts the events of the 1997 IBM challenge, following Kasparov's 1996 defeat of Deep Blue. It seeks to support Kasparov's own account of the two chess matches, and also to present a brief version of the reasoning presented in the previous article.